Mitral valve repair versus replacement - Mick, Stephanie L.; Keshavamurthy, Suresh; Gillinov, A. Marc (Annals of Cardiothoracic Surgery, 2015)
Degenerative, ischemic, rheumatic and infectious (endocarditis) processes are responsible for mitral valve disease in adults. Mitral valve repair has been widely regarded as the optimal surgical procedure to treat mitral valve dysfunction of all etiologies. The supporting evidence for repair over replacement is strongest in degenerative mitral regurgitation. The aim of the present review is to summarize the data in each category of mitral insufficiency and to provide recommendations based upon this data.